2011
DOI: 10.1177/1045389x11425281
|View full text |Cite
|
Sign up to set email alerts
|

On the dynamic behavior of piezoelectric active repair by the boundary element method

Abstract: The dynamic behavior of piezoelectric active repair bonded on cracked structures is analyzed in this article. The boundary\ud element code used to perform the simulations is implemented in the framework of piezoelectricity in order to\ud model the coupling between the elastic and the electric fields, which represents the most important feature of piezoelectric\ud media. The fracture mechanics problem, i.e. the crack, as well as the bonding layer between the host structure and\ud the active patch is modeled by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…Another method of repair is based on the boundary element method developed by Alaimo et al [33,34]. In this approach, the damaged structure considered was isotropic, and characterized by the behaviour of dynamic fracture mechanics.…”
Section: Active Repair Of Isotropic Materialsmentioning
confidence: 99%
“…Another method of repair is based on the boundary element method developed by Alaimo et al [33,34]. In this approach, the damaged structure considered was isotropic, and characterized by the behaviour of dynamic fracture mechanics.…”
Section: Active Repair Of Isotropic Materialsmentioning
confidence: 99%
“…Different methodologies used for the active stress control and repair via the piezoelectric actuator [5][6]. Reduction of the stress concentration near notches and holes using the piezoelectric actuators was investigated by Rogers [7]. The study, conducted by Shah et al [8], found that 33 % of stress concentration on a finite plate with a hole can be obtain using the active piezoelectric actuator.…”
Section: Introductionmentioning
confidence: 99%
“…The basic idea in their research is to induce stress with the piezoelectric actuator in the singular area at the crack tip in order to counteract the external load. Several methodologies have been developed to study the active repair of the cracked structure [3][4][5][6][7][8][9][10][11][12][13][14]. Due to their electromechanical coupling effects, piezoelectric materials are commonly used as sensors or actuators in various engineering structures.…”
Section: Introductionmentioning
confidence: 99%